Assessment of Antibiotic Resistance and Efflux Pump Gene Expression in Neisseria Gonorrhoeae Isolates from South Africa by Quantitative Real-Time PCR and Regression Analysis - Mitchev, Nireshni; Singh, Ravesh; Ramsuran, Veron; Ismail, Arshad; Allam, Mushal; Kwenda, Stanford; Mnyameni, Florah; Garrett, Nigel; Swe Swe-Han, Khine; Niehaus, Abraham J.; Mlisana, Koleka P. (International Journal of Microbiology, 2022)
Introduction. Treatment of gonorrhoea infection is limited by the increasing prevalence of multidrug-resistant strains. Cost-effective molecular diagnostic tests can guide effective antimicrobial stewardship. The aim of this study was to correlate mRNA expression levels in Neisseria gonorrhoeae antibiotic target genes and efflux pump genes to antibiotic resistance in our population. Methods. This study investigated the expression profile of antibiotic resistance-associated genes (penA, ponA, pilQ, mtrR, mtrA, mtrF, gyrA, parC, parE, rpsJ, 16S rRNA, and 23S rRNA) and efflux pump genes (macAB, norM, and mtrCDE), by quantitative real-time PCR, in clinical isolates from KwaZulu-Natal, South Africa. Whole-genome sequencing was used to determine the presence or absence of mutations. Results. N. gonorrhoeae isolates, from female and male patients presenting for care at clinics in KwaZulu-Natal, South Africa, were analysed. As determined by binomial regression and ROC analysis, the most significant (p≤0.05) markers for resistance prediction in this population, and their cutoff values, were determined to be mtrC (p=0.024; cutoff <0.089), gyrA (p=0.027; cutoff <0.0518), parE (p=0.036; cutoff <0.0033), rpsJ (p=0.047; cutoff <0.0012), and 23S rRNA (p=0.042; cutoff >7.754). Conclusion. Antimicrobial stewardship includes exploring options to conserve currently available drugs for gonorrhoea treatment. There is the potential to predict an isolate as either susceptible or nonsusceptible based on the mRNA expression level of specific candidate markers, to inform patient management. This real-time qPCR approach, with few targets, can be further investigated for use as a potentially cost-effective diagnostic tool to detect resistance.